Azathioprine allows glucocorticoid withdrawal – post hoc results of a prospective study in patients with inflammatory bowel diseases - Teich, Niels; Mohl, Wolfgang; Bokemeyer, Bernd; Bündgens, Burkhard; Büning, Jürgen; Miehlke, Stephan; Hüppe, Dietrich; Maaser, Christian; Siegmund, Britta; Schmidt, Carsten; Stallmach, Andreas; on behalf of the German IBD Study group (Zeitschrift für Gastroenterologie, 2017)
Background Azathioprine is recommended as first-line immunosuppressant in patients with steroid-dependent inflammatory bowel diseases (IBDs). However, data on steroid withdrawal after induction therapy in IBD patients are sparse.Methods In this post-hoc analysis of a prospective multicenter study, we analyzed the proportion and clinical characteristics of 324 azathioprine-tolerant patients as to whether they could terminate the glucocorticoid therapy after initiation of treatment with azathioprine.Results Systemic steroid therapy was required in 190 patients (58.6 %) at baseline and in 40 patients (12.3 %) at the end of the follow-up period (p < 0.001). The median daily dose was 30 mg at baseline and 10 mg at follow-up. At baseline, only 122 patients (37.2 %) were advised to take at least the lowest recommended dose of 2 mg/kg per day. At follow-up, 221 patients (68.2 %) were prescribed at least the recommended maintenance dosage.Conclusion The majority of patients with thiopurine-naïve IBDs that needed systemic steroids at baseline were able to discontinue steroids after 3 – 6 months of azathioprine therapy. These data support the continued high value of azathioprine in the immunosuppressive therapy of IBD.
Keywords: Morbus Crohn; Colitis ulcerosa; Steroidtherapie; chronisch entzündliche Darmerkrankung